2010
DOI: 10.1111/j.1740-0929.2009.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyphenols extracted from Tamarind (Tamarindus indica L.) seed coat on physiological changes, heterophil/lymphocyte ratio, oxidative stress and body weight of broilers (Gallus domesticus) under chronic heat stress

Abstract: The aim of this experiment was to determine the effect of polyphenols extracted from tamarind (Tamarindus indica L.) seed coat on physiological changes, oxidative stress and production of male broilers maintained at high environmental temperatures. The results found that body temperature and respiratory rate of broilers maintained at 38 +/- 2 degrees C was higher than broilers maintained at 26 +/- 2 degrees C (P < 0.05). On day 1, the heterophil/ lymphocyte ratio of broilers maintained at 38 +/- 2 degrees C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 37 publications
6
27
0
4
Order By: Relevance
“…It is expected that the potential effect of ETS in preventing further accumulation of free radicals as well as oxidative stress could be due to the ability to reduce free radical formation or through the free radical scavenging activity. Moreover, the previous reports on tamarind seed coat extract have specified increase in the antioxidant enzymes and a decrease in the oxidative stress [9, 10]which is in confirmation with present findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is expected that the potential effect of ETS in preventing further accumulation of free radicals as well as oxidative stress could be due to the ability to reduce free radical formation or through the free radical scavenging activity. Moreover, the previous reports on tamarind seed coat extract have specified increase in the antioxidant enzymes and a decrease in the oxidative stress [9, 10]which is in confirmation with present findings.…”
Section: Discussionsupporting
confidence: 93%
“…Various parts of T. indica have been reported for a multitude of health benefits such as antioxidant, antihepatotoxic, antiinflammatory, antimutagenic, carminative, and expectorant properties [9]. However, the therapeutic potential of T. indica seed coat remains largely unexplored, although free radical scavenging activity and total phenolics content of tamarind seed coat extract have been demonstrated in various studies [9, 10]. Pumthong [11] reported that tamarind seed coat is composed of polyphenols including tannins, anthocyanidin, and oligomericanthocyanidins.…”
Section: Introductionmentioning
confidence: 99%
“…No RR and CT differences (p>0.05) among genotypes were detected in none of the experimental weeks. The considerable RR increase in chickens under heat stress was in agreement with several previous reports (Abu -Dieyeh, 2006;Aengwanich & Suttajit, 2010). Body heat dissipation increased with increasing RR, but CT remained unchanged.…”
Section: Effect Of Hsp70 Genotypes On Physiological Responsessupporting
confidence: 81%
“…When chickens are exposed to heat stress, the content of lymphocytes and monocytes in the blood decreases and the number of heterophils increases, i.e., the H/L ratio increases (Aengwanich and Suttajit, 2010; Ruell et al, 2014). The present study showed that the variation in the trend of H and H/L values was similar in the 2 breeds of broilers under heat stress and no heat stress conditions.…”
Section: Discussionmentioning
confidence: 99%